2017
DOI: 10.1186/s13104-017-2573-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and risk factors of neonatal sepsis among neonates in Felege Hiwot referral Hospital, Bahir Dar, Amhara Regional State, North West Ethiopia 2016: a retrospective chart review

Abstract: BackgroundSepsis remains a major cause of morbidity and mortality among neonates. The risk factors and clinical outcomes of sepsis are poorly understood. Most cases of sepsis occurred mostly within the first week of newborns life related to perinatal risk factors. Late onset sepsis is related to hospital acquired infections which is seen after seven days of age. The purpose of this study was to assess clinical outcome and risk factors of neonatal sepsis in Felege Hiwot referral hospital Bahir Dar, North West E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
50
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 25 publications
(26 reference statements)
14
50
5
3
Order By: Relevance
“…The study conducted in Ethiopia indicated that around 15% of meningitis clients might end up with unwanted outs comes of which death is one of it. This finding is relatively lower than the current study result [26]. The difference might be because the study in Bahr Dar, Ethiopia was done for a short period of time that might be associated with difficulties in estimating the exact number within a short time.…”
Section: Fig 1 Organisms Isolated From Csf Cultures Of Patients Of contrasting
confidence: 92%
“…The study conducted in Ethiopia indicated that around 15% of meningitis clients might end up with unwanted outs comes of which death is one of it. This finding is relatively lower than the current study result [26]. The difference might be because the study in Bahr Dar, Ethiopia was done for a short period of time that might be associated with difficulties in estimating the exact number within a short time.…”
Section: Fig 1 Organisms Isolated From Csf Cultures Of Patients Of contrasting
confidence: 92%
“…CSF sample collection after prior antimicrobial treatment could obviously contribute to culture negative results. The overall prevalence of bacterial meningitis of the current study was also lower than study conducted in Bahr Dar that reported a prevalence of 69.8% (33). This difference could be due to difference diagnostic method.…”
Section: Discussioncontrasting
confidence: 78%
“… 46 However, contrasting findings were observed in earlier studies conducted in different parts of the world. 9 44 47 48 49 Early rupture of membrane and prolonged labor increases the chance of ascending microorganisms from the birth canal into the amniotic sac and fetal compromise as well as asphyxia which frequently leads to sepsis in the neonatal period. 50 This finding could serve as justification for prophylactic antibiotic therapy for neonates born to mothers with a history of PROM during pregnancy.…”
Section: Discussionmentioning
confidence: 99%